Effects of cross-border mergers and acquisitions on GDP per capita and domestic investment in transition countries - Zvezdanović Lobanova, Jelena; Kračun, Davorin; Kavkler, Alenka (Journal of Business Economics and Management, 2018)
The study investigates the impact of cross-border mergers and acquisitions on GDP per capita and domestic investment in 22 European transition countries from 2000 to 2014 by using the system Generalized Method of Moments estimator. The main implications are that cross-border mergers and acquisitions have a negative effect on GDP per capita in the year of merger or acquisition, while their lagged level shows a positive impact. From long-term perspective, this type of FDI has negative and significant effect on GDP per capita. The results show that one-year lagged cross-border mergers and acquisitions positively affects domestic investment, suggesting that spillover effects of this type of investment can be expected not earlier than one year after the merger or acquisition. The value of this paper is that our results show how the advances in structural reforms enhance GDP per capita whereas their influence on domestic investment activity is insignificant. We found that there is insignificant impact of the relationship between overall structural reforms and cross-border mergers and acquisitions on GDP per capita and domestic investment both in short and long run. The originality of this study lies in investigation of the dynamic nature of cross-border mergers and acquisitions and their economic effects depending on the quality of structural reformss.